Anthropometric characteristics of Malay nose- A Pilot Study / Tengku Fazrina Tengku Mohd Ariff ... [et al.] - Tengku Mohd Ariff, Tengku Fazrina; Muhamad Hanafi, Farah Farhana; Abdul Razak, Nur Wardah Hanis; Chaiprakit, Narissaporn; Abdul Wahab, Hazmyr (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Anthropometric analysis provides the most reliable comparison of the body forms by using specific landmarks determined in respect of anatomical prominences. The knowledge of unique shape, anatomy and dimensions of the nose is very useful for surgeon undertaking its repair and reconstruction. Prosthetic rehabilitation also requires the ability to imagine the position and dimension of the nose within the facial proximity. Therefore, the access to nasal data for each population are advantageous. The aims were to measure parameters of external nose of a Malay population and to determine the significant difference in nose value parameters between gender and age group. The direct anthropometric measurements were carried out in 86 Malay subjects within the age range of 18 to 55 years old who attended UiTM dental clinic. Nasal landmarks were identified, and the nose parameters were measured using digital calliper. The values were expressed as mean, standard deviation and range. Nasal height, width and length of the nasal bridge were higher in male. The intercanthal width and philtrum length were statistically not significant for both genders. There were significant differences in nasal width, philtrum length, intercanthal width and outer intercommisural mouth width between the three age groups. However, the height of the nose, length of the nasal bridge and nasal index between age group were statistically not significant. The male population and the 41-55 years age group have higher nose value parameters. The most common type of nose was platyrrhine: broad. This study also suggested that Malay population have medium broad nose as the nasal index for both genders was ≤ 84.90.